2017
DOI: 10.3892/ol.2017.7270
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-associated antigen 9 is upregulated in hepatocellular carcinoma tissue and enhances QGY cell proliferation and invasion in�vitro

Abstract: Abstract.The incidence and mortality rates of hepatocellular carcinoma (HCC) are higher in China compared with in other countries. Further research is required in order to improve the diagnosis and treatment of HCC. Sperm-associated antigen 9 (SPAG9) protein has been revealed to serve an important function in cancer progression; however, the underlying mechanisms remain to be elucidated. The present study investigated the expression level of SPAG9 in HCC tissues using quantitative-polymerase chain reaction, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We carefully reviewed previous studies on the role of SPAG9 in different tumor-cell lines and summarized the results [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] ( Table S5 ). We noted that in addition to promoting proliferation, migration, and EMT, SPAG9 also promotes autophagy in several tumor-cell lines [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We carefully reviewed previous studies on the role of SPAG9 in different tumor-cell lines and summarized the results [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] ( Table S5 ). We noted that in addition to promoting proliferation, migration, and EMT, SPAG9 also promotes autophagy in several tumor-cell lines [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sperm-associated antigen 9 ( SPAG9 ) is a cancer-testis antigen expressed in various tumor tissues, which has two main alternative spliceosomes—JLP (1307 amino acids) and SPAG9 (766 amino acids). It plays a wide role in tumor-cell lines: it not only promotes proliferation, migration, and epithelial–mesenchymal transition (EMT) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], but also regulates autophagy [ 18 , 19 ]. A previous study found that SPAG9 overexpression promotes proliferation and migration in the ccRCC cell lines Caki-1 and NII-AKS413 [ 4 ]; however, studies on the prognostic value of SPAG9 in ccRCC patients are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…6, left panel). Notably, our previous study discovered that SPAG9 depletion caused cell cycle arrest in the G1-G2 phase in QGY-7703 cells (10); however, in HepG2 cells, the cell cycle was arrested in the S phase. We speculated that this difference is due to the different types of liver cancer from which these two cell lines were derived: QGY-7703 cells were derived from a hepatocellular carcinoma, but HepG2 cells were derived from a hepatoblastoma (19), and the specific regulatory mechanism of SPAG9 in the cell cycle and apoptosis requires further exploration.…”
Section: Discussionmentioning
confidence: 95%
“…It can be overexpressed in tumors of the ovary, breast, lung and bone (5)(6)(7), and the expression of SPAG9 in tumor tissues is correlated with progression and prognosis of cancer patients (8,9). We previously demonstrated that SPAG9 was overexpressed in liver cancer (10), however, how SPAG9 influences liver cancer progression is not yet clear. In the present study, we analyzed the function of SPAG9 in the liver cancer-derived HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm-associated antigen 9 (SPAG9) gene is located on human chromosome 17q21.33 and encodes a protein of 766 amino acids that is highly expressed in cancer and contributes to the occurrence and development of tumors [8][9][10]. Moreover, silencing of SPAG9 inhibited liver cancer, cervical cancer and kidney cancer [10][11][12].…”
Section: Introductionmentioning
confidence: 99%